Predatory fireflies and their toxic firefly prey have evolved distinct toxin resistance strategies. - Yang, L.; Borne, F.; Betz, A.; Aardema, M.L.; Zhen, Y.; Peng, J.; Visconti, R.; Wu, M.; Roland, B.P.; Talsma, A.D.; Palladino, M.J.; Petschenka, G.; et al. (Current Biology, 2023)
Toxic cardiotonic steroids (CTSs) act as a defense mechanism in many firefly species (Lampyridae) by inhibiting a crucial enzyme called Na[+],K[+]-ATPase (NKA). Although most fireflies produce these toxins internally, species of the genus Photuris acquire them from a surprising source: predation on other fireflies. The contrasting physiology of toxin exposure and sequestration between Photuris and other firefly genera suggests that distinct strategies may be required to prevent self-intoxication. Our study demonstrates that both Photuris and their firefly prey have evolved highly resistant NKAs. Using an evolutionary analysis of the specific target of CTS (ATP?) in fireflies and gene editing in Drosophila, we find that the initial steps toward resistance were shared among Photuris and other firefly lineages. However, the Photuris lineage subsequently underwent multiple rounds of gene duplication and neofunctionalization, resulting in the development of ATP? paralogs that are differentially expressed and exhibit increasing resistance to CTS. By contrast, other firefly species have maintained a single copy. Our results implicate gene duplication as a facilitator in the transition of Photuris to its distinct ecological role as a predator of toxic firefly prey.